The impact of the global financial crisis on Moroccan exports: a gravity model approach - Lahrech, Abdelmounaim (2019)
Purpose– The purpose of this paper is to examine the impact of the global financial crisis (GFC) on Morocco’s export performance employing a gravity model framework. Design/methodology/approach– The authors investigate trade flows between Morocco and its 18 major trading partners from 2001 to 2015. The authors employ a trade gravity model using a first-order Taylor approximation of multilateral resistance terms and estimate by OLS and PPML. Findings–Morocco’s export performance was affected by the GFC. The authorsfind evidence that the fall in aggregate demand from Morocco’s trading partners, particularly in Europe, led to a fall in its exports. The authors also find that Morocco’s exports are positively correlated with the market size of its partner but negatively associated with distance. Originality/value– This study contributes to the literature in two distinct ways. First, it examines variables affecting export performance in one of the emerging markets in the Middle East and North Africa region. Second, it assesses empirically whether there is a relationship between the GFC and the decline in Moroccan exports. The study also provides a number of important implications for policy makers and academics.